Effect of Dietary Ramie Powder at Various Levels on the Growth Performance, Meat Quality, Serum Biochemical Indices and Antioxidative Capacity of Yanling White Geese - Chen, Fengming; He, Jieyi; Wang, Xin; Lv, Tuo; Liu, Chunjie; Liao, Liping; Li, Zibo; Zhou, Jun; He, Bingsheng; Qiu, HuaJiao; Lin, Qian (Animals (Basel), 2022)
To investigate the effects of different levels of ramie powder (Boehmeria nivea (L.) Gaudich.) (i.e., 0%, 6%, 12% and 24%) on the production performance, serum biochemical indices, antioxidative capacity and intestinal development of Yanling white geese, a total of 256 geese at 56 days of age were randomly divided into four groups and fed a control diet and the control diet supplemented with 6%, 12% and 24% ramie powder, respectively, for 42 days. The results show that dietary supplementation with 12% ramie powder significantly increased the average final weight (p < 0.05) and tended to improve the average daily gain (ADG) and feed/gain ratio (F/G) of the test geese (0.05 < p < 0.10). Moreover, the dietary inclusion of 12 and 24% ramie powder improved meat qualities by reducing the L* value (p < 0.05) and cooking loss (0.05 < p < 0.10) of thigh muscle. Compared with the control group, the ramie powder supplementation at different levels increased the serum activities of glutathione peroxidase and glutathione, promoting the antioxidative capacity of the body (0.05 < p < 0.10). This study demonstrates that moderate ramie powder is beneficial to the production performance of Yanling white geese and has the potential to be used as a poultry feed ingredient. In conclusion, 12% was the proper supplementation rate of ramie powder in Yanling white geese feed.